The Impact of Work Family Conflict, Role Conflict, and Burnout on Intention to Quit of Female Employees - Purnawati, Ni Luh Gede Putu; Adhika, I Nyoman Resa; Yuliastuti, Ida Ayu Nyoman (AIBPM Publisher, 2020)
This study was conducted to determine the effect of work family conflict, role conflict and burnout on the Intention to quit female employees in the Village Credit Institute (LPD) of Gianyar Regency. The samples used was 90 female employees in 270 LPDs of Gianyar Regency. By using multiple linear regression analysis techniques, the results obtained are work family conflict and role conflict have a positive effect on intention to quit, but burnout does not affect the intention to quit female employees in LPDs of Gianyar Regency. The research implication is that the higher work family conflict and the role conflict of female employees in their work, the higher the desire for female employees to leave their work.